2022
DOI: 10.1039/d2tc01036d
|View full text |Cite
|
Sign up to set email alerts
|

Referential tuning strategy for high-lying triplet energy level setting in OLED emitter with hot-exciton characteristics

Abstract: “Hot-exciton” emitters featured with high-lying reverse intersystem crossing (hRISC) has been served as promising candidates due to their meliorative exciton utilization efficiency and efficiency roll-off in organic light-emitting diodes (OLEDs)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…This hypothesis was proven by comparing two D-A-D molecules that combined a naphtho[2,3-d][1,2,3]triazole (NMZ) core and either naphthalene (Np) or anthracene (An) substituents. The T 1 energy of Np was higher than the T 1 energy of An, and, subsequently, Np-NMZ-Np had a larger T 2 -T 1 energy gap than An-NMZ-An [80]. In addition, for a D-A type molecule, the electronic coupling between LE T 1 and CT T 2 states correlates with the electron exchange between the donor and the acceptor fragments.…”
Section: Hot Exciton Materials Designmentioning
confidence: 91%
See 2 more Smart Citations
“…This hypothesis was proven by comparing two D-A-D molecules that combined a naphtho[2,3-d][1,2,3]triazole (NMZ) core and either naphthalene (Np) or anthracene (An) substituents. The T 1 energy of Np was higher than the T 1 energy of An, and, subsequently, Np-NMZ-Np had a larger T 2 -T 1 energy gap than An-NMZ-An [80]. In addition, for a D-A type molecule, the electronic coupling between LE T 1 and CT T 2 states correlates with the electron exchange between the donor and the acceptor fragments.…”
Section: Hot Exciton Materials Designmentioning
confidence: 91%
“…Although the hot exciton process does not obey Kasha's rule, numerous hot exciton materials have been reported [20,[68][69][70][71][72][73][74][75][76]. A comprehensive review on the reported cases of hot exciton materials can be found elsewhere [20], and some representative molecules are shown in Figure 5 [51, [77][78][79][80][81][82][83] with their photophysical properties summarized in Table 1. Ideally, hot exciton materials have several advantages.…”
Section: Hot Exciton Processmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] The efficient hRISC occurs only by suppressing internal conversion (IC) from the T n -T 1 state. [23][24][25] The RISC and IC rates are inversely proportional to the T n -S m energy gap. [26] Besides the small T n -S m gap, spin-orbit coupling (SOC) plays a prominent role in determining the RISC rate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] It is well‐known that hot excitons on high‐lying excited triplet state energy levels can theoretically realize the exciton utilization of 100% by fast reverse intersystem crossing (hRISC) from T n (n≥ 2) to S m (m≥ 1). [ 15 ] Therefore, if using hot exciton materials as EEL, triplet excitons on T n can be utilized directly without the need for collisions of the triplet exciton pairs that leads to additional energy loss. It is expected that the efficiency of TTF‐based blue fluorescence OLEDs can achieve further large enhancement.…”
Section: Introductionmentioning
confidence: 99%